Recent highlights in advanced functional materials and biomedical research selected, peer reviewed papers from the 8th International Conference on Molecular Imprinting (MIP 2014), September 18-21, 2014, Zhenjiang, China - Yuan, Xinhua (Key engineering materials, 2015)
Collection of selected, peer reviewed papers from the 8th International Conference on Molecular Imprinting (MIP 2014), September 18-21, 2014, Zhenjiang, China. The 37 papers are grouped as follows: Chapter 1: Engineering Materials; Chapter 2: Biotechnologies and Biomedical Engineering.